Los “Youtubers” como modalidad emergente de producción audiovisual en el Perú - Osorio Bazan, Jose Ramon (2020)
The purpose of this research was to analyze youtubers as an emerging modality of audiovisual production in Peru. For this, we worked on the basis of the qualitative approach. The study sample was composed of an audiovisual producer, a digital media analyst and three Peruvian youtubers; the interview guide was used as an instrument for data collection. Regarding the conclusions, it is highlighted how digital media follow the same stages of production as traditional media, but in a less rigid and professional way; thus, incipient economic results are obtained for the first group. However, the interactivity that brings the digital platforms and the preference of the young target towards it, has forced the traditional media to transform and adapt progressively; and Peru has not been oblivious to that situation.